Vasomotor oscillation in vibration-induced white finger. - Pyykko, I.; Gemne, G.; Kolari, P.; Starck, Jukka; Ilmarinen, Raija; Aalto, H. (Scandinavian Journal of Work, Environment & Health, 1986)
Vasomotor oscillation at different ambient temperatures, with and without anesthesia of the finger nerves, was studied in six persons with vibration-induced white finger (VWF) and in 10 referents. The power spectral density (PSD) of the Fourier transform of the laser-Doppler flowmeter signal from the finger pad vessels was analyzed. In both groups, the PSD of the vasomotor oscillation in the frequency range of 0.05-0.25 Hz was more pronounced in a cold than in a hot environment. Without finger nerve anesthesia, the oscillations of the referents were significantly greater (p less than 0.01) than those of the VWF subjects (PSD -34.4 dB and -41.6 dB, respectively). With anesthesia of the finger vasomotor nerves, the PSD was reduced in both groups. In the anesthetized finger there was no statistically significant group difference. Thus the myogenic component of the vasomotor activity was the same in the referents as in the VWF subjects. The results show that the autonomic neural influence on vasomotor oscillation in skin of the finger pad is weaker in persons with VWF. This weakness may be a sign of peripheral neuropathy, which may lead to a denervation syndrome causing hypersensitivity of the adrenoceptors to cold.